2001
DOI: 10.1590/s1517-83822001000300017
|View full text |Cite
|
Sign up to set email alerts
|

Occurrency of Malassezia Pachydermatis and Other Infectious Agents as Cause of External Otitis in Dogs From Rio Grande Do Sul State, Brazil (1996/1997)

Abstract: The purpose of this work was to evaluate the frequency of Malassezia pachydermatis infection and other infectious agents in dogs with external otitis and with healthy auditory tubes. Clinical manifestations of external otitis were evaluated. Samples from the auditory tube of 102 dogs with otitis and from 32 healthy dogs were submitted to direct microscopic examination and cultured in blood agar and Sabouraud dextrose agar with chloramphenicol and cycloheximide. Direct examination showed more than ten cells of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
14

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 5 publications
1
13
1
14
Order By: Relevance
“…Vários estudos têm descrito a presença de microrganismos constituintes de uma microbiota normal no ouvido canino e têm demonstrado a associação entre S. intermedius e M. pachydermatis nos quadros de OE canina (Junco e Barrasa, 2002;Lilenbaum et al, 2000;Nobre et al, 2001). Embora alguns estudos considerem os estafilococos coagulase-negativos como o principal agente de OE canina (Lilenbaum et al, 2000), neste estudo o S. intermedius foi a bactéria mais freqüente.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Vários estudos têm descrito a presença de microrganismos constituintes de uma microbiota normal no ouvido canino e têm demonstrado a associação entre S. intermedius e M. pachydermatis nos quadros de OE canina (Junco e Barrasa, 2002;Lilenbaum et al, 2000;Nobre et al, 2001). Embora alguns estudos considerem os estafilococos coagulase-negativos como o principal agente de OE canina (Lilenbaum et al, 2000), neste estudo o S. intermedius foi a bactéria mais freqüente.…”
Section: Resultsunclassified
“…pachydermatis é um microrganismo que compõe as microbiotas auricular e dérmica de carnívoros domésticos, embora possa apresentar patogenicidade em diversas situações (Mansfield et al, 1990;Leite et al, 2003). Para a OE, estes resultados assemelham-se aos relatados por Nobre et al, (2001) (76,5%) e Crespo et al, 2000 (68,4%). Quanto à OM, os resultados confirmam os da literatura, demonstrando a pouca participação dos microrganismos fúngicos nesses quadros (Harvey et al, 2004).…”
Section: Resultsunclassified
“…Animais de qualquer idade, sexo ou raça são susceptíveis à infecção, embora a doença apresente tendência a ser mais comum em animais jovens, debilitados e velhos (MORIELLO, 2004 Neste estudo, as otites ocorreram mais nas raças poodle (24,44%), lhasa apso (15,55%)e cocker spaniel inglês (13,33%), semelhantes ao descrito por outros autores (LEITE, 2000;NOBRE et al, 2001;OLIVEIRA et al, 2005). Os cães sem raça definida representaram 15,55% dos casos de otites.…”
Section: Introductionunclassified
“…Although M. pachydermatis is frequently isolated from external otitis processes, there is not consensous regarding its prevalence as an etiologic agent of the same, being reported between 5.12% and 76.5% (5,19,20). In studies done by Boehriger (22) they reported a prevalence of 62% for cytology and 49% by culture (morphological macro/ microscopic and Sabouraud agar growth without lipid supplement), the difference between these data could be due to the methodology used in this study, since specific metabolic test were performed which allowed to identify M. pachydermatis by 31.1% and M. furfur in 12.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque M. pachydermatis es frecuentemente aislada de procesos de otitis externa, no hay consenso respecto a su prevalencia como agente etiológico de la misma, encontrándose reportes entre 5.12% y 76.5% (5,19,20). En estudios realizados por Boehriger (22) se reportó una prevalencia de 62% para citología y 49% para cultivo (caracterización morfológica macro/microscópica y crecimiento en agar sabouraud sin suplemento lipídico), la diferencia entre estos datos puede deberse a la metodología utilizada en este estudio, dado que se llevaron acabo pruebas metabólicas específicas para identificar M. pachydermatis en un 31.1% y M. furfur en el 12.6%.…”
Section: Discussionunclassified